Rietveld Refinement of MIL‐160 and Its Structural Flexibility Upon H2O and N2 Adsorption - Wahiduzzaman, Mohammad; Lenzen, Dirk; Maurin, Guillaume; Stock, Norbert; Wharmby, Michael T. (European journal of inorganic chemistry, 2018)
The porous metal‐organic framework (MOF) MIL‐160 [Al(OH)(O2C‐C4H2O‐CO2)] was investigated by means of high‐resolution powder X‐ray diffraction experiments using synchrotron radiation. The structures of the dehydrated, hydrated and nitrogen loaded forms of MIL‐160 are refined by the Rietveld method. The structure of the hydrated form, as postulated from solid state NMR and DFT calculations, is confirmed. The host–guest and thermal responses of this compound are also investigated. Adsorption of water is found to induce a phase transition from I41/amd (the dehydrated structure) to I41md (the hydrated structure), mediated by flexibility of the MOF framework. Water molecules were observed to arrange themselves with an ice‐like geometry. Conversely, adsorption of more weakly interacting N2 into the structure or thermal treatment (cooling the sample from 400 to 80 K) leads to no phase transition, indicating that the phase transition is induced by the strong interactions of H2O with the framework. The accuracy of the refined structures is investigated by DFT calculations, which show very small deviations in optimised atomic positions and lattice parameters. The structure of Al‐MOF MIL‐160 [Al{OH(O2C‐C4H2O‐CO2)}], postulated from solid state NMR and DFT calculations, is confirmed by Rietveld refinement of high‐resolution synchrotron powder X‐ray diffraction. Its H2O and N2 host–guest complexes were also refined & demonstrate structural flexibility. DFT calculations demonstrate the high‐accuracy of the refined structures.